Debt Maturity: A Review of The Literature - Kristiana Sri Utami; Bhenu Artha; Sakhira Tarisa Sofia Amirullah; Safira Wulan Agustin (Yayasan Adra Karima Hubbi, 2024)
Background. Financial crises and rollover risk are closely associated with short-term debt, which impacts a company’s ability to undertake long-term investments and affects the state of the economy. Short-term debt reduces asset volatility and increases the distance to default compared to long-term debt. A significant factor influencing decisions on debt maturity is borrowers’ awareness of their default risk. Purpose. The study aims to identify the variables that influence and are influenced by debt maturity. It focuses on understanding the relationship between debt maturity, disproportional control rights, capital age, and asset life. Method. This research employs a theoretical literature review to analyze the relationships between the identified variables. By synthesizing existing theories, the study develops a conceptual framework to explore the impact of disproportional control rights on debt maturity and its downstream effects on financial management. Results. The findings reveal that disproportional control rights significantly influence debt maturity. Companies with longer-term debt structures are better positioned to manage capital age and asset life effectively. Conversely, short-term debt structures tend to align with younger capital and shorter asset lifespans, often limiting long-term operational sustainability. Conclusion. The study concludes that companies must carefully consider debt maturity in their financial strategies to ensure stability and sustainable growth. Disproportional control rights, capital age, and asset life are crucial factors to manage. Further empirical research is recommended to validate and expand the findings, providing practical insights into optimizing debt maturity in diverse organizational contexts.